Penerapan Metode E-Service Quality Terhadap Pengukuran Tingkat Kepuasan Penggunaan Marketplace - Parwita, Wayan Gede Suka; Indradewi, I Gusti Ayu Agung Diatri; Ariantini, Made Suci; Ginantra, Ni Luh Wiwik Sri Rahayu; Putra, I Kadek Andika (Prahasta Publisher, 2022)
Intense competition makes various existing markets must be able to provide the best and satisfaction for users to win the existing competition. In the review of the JD.ID application during versions 6.3 and 6.4 there were several user complaints that led to system and service quality problems. Service quality is one of the factors supporting the success or failure of an information system to provide satisfaction to its users. The purpose of this study was to determine how the influence of electronic service quality (e-service quality) on user satisfaction in the JD.ID application. The type of analysis used in this study is simple regression analysis with descriptive analysis to describe a generalization or explain the research subject based on the dimensions of e-service quality, so that an overview of the effect of e-service quality on user satisfaction can be obtained. The processed data was obtained from distributing questionnaires by using the google form. The results showed that the majority of JD.ID marketplace users in Badung Regency were women. The test results show that e-service quality which consists of dimensions of efficiency, system availability, fulfillment, privacy, responsiveness, compensation, and contact has a significant influence on user satisfaction and has a strong correlation, meaning that the higher the service quality JD has. ID, the higher the level of satisfaction of JD.ID users. It can be said that the service quality of JD.ID is quite good in providing user satisfaction.